THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN MEDIATING WORK STRESS AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Pujiastuti, Erni; Marwan, Jubery; Rahayu (Universitas prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyse the role of transformational leadership in mediating the influence of work stress and work motivation on employee performance. The research was conducted at the Intelligence and Security Agency (Baintelkam) of the Indonesian National Police using a quantitative approach and path analysis method. The sample consisted of 126 respondents selected through purposive sampling. Data were collected using questionnaires and tested for validity, reliability, and regression assumptions. Path analysis using the help of the sobel-test application. The findings reveal that work stress does not significantly affect transformational leadership or employee performance. conversely, work motivation positively and significantly influences transformational leadership and employee performance. Transformational leadership also mediates the relationship between work motivation and employee performance but does not mediate the effects of work stress on performance. These results underscore the importance of transformational leadership in enhancing work motivation and improving employee performance. However, addressing the effects of work stress requires additional measures, such as creating a more adaptive work environment. Practically, this study highlights the need for organisations to strengthen transformational leadership capacity and prioritise managing employee motivation and stress to foster a productive and conducive workplace.